Diagnosing moyamoya syndrome using ultrasound - a case report. Issue 1 (December 2015) - Braun, Tobias; Juenemann, Martin; Gündüz, Dursun; Schmetsdorf, Stefanie; Roessler, Florian; Grams, Astrid; Gramsch, Carolin; Tanislav, Christian
Abstract Background Moyamoya syndrome is a vasculopathy characterised by progressive occlusion of the cerebral arteries resulting in the development of abnormal collateral circulation. To diagnose this syndrome, imaging of the cerebral arteries is required including CT- or MR-angiography and conventional angiography. We present a case of moyamoya disease with typical findings detected in the sonography. The diagnosis was suspected after reviewing the initial ultrasound images of the cerebral arteries with evidence for obliterated intracranial arteries and the detection of an existing collateral circulation network. Case presentation A 62 years old male patient presented in the hospital's emergency department with symptoms indicating a subacute cerebrovascular event. Immediate sonographic studies showed a right-sided pulsatile Doppler-signal in the common and internal carotid arteries, suggestive of distal stenoses. In addition, the transcranial examination indicated obliteration of both middle cerebral arteries. Numerous arterial vessels suggestive of leptomeningeal collateral arteries revealed a strong arterial leptomeningeal flow. At this stage of the diagnostic work-up, the collateral circulation network, characteristic of moyamoya disease, was indicated by sonography. Moyamoya syndrome was verified by conventional angiography. The aetiological work remained empty, so the diagnosis of moyamoya disease was established. Conclusion Our case report indicates that sonography can be a useful tool for detecting the vaculopathy in moyamoya syndrome. In case routine procedures, such as the CT- or MR-angiography, with evidence for obliterated intracerebral arteries, ultrasound studies might provide important information regarding an existing collateral network in the scope of a moyamoya syndrome.